(untitled) (Research, Society and Development, 2024)
Cholelithiasis commonly remains asymptomatic, although the obstruction of the cystic duct can occur, generating symptoms. The objective of the study was to understand the epidemiological profile of individuals who died from cholecystitis in the Northeast region, from 2013 to 2022, and to comprehend the associated aspects of this mortality. This is an epidemiological, observational, descriptive study, with a quantitative approach, utilizing data from the Department of Information of the Unified Health System (DATASUS) via the Mortality Information System (SIM). The investigated variables included the number of deaths, mortality rate, gender, age group, race/ethnicity, marital status, and education level. The study identified a total of 3,847 deaths due to cholecystitis in the Northeast region, with a growing trend during the study period. The state of Bahia had the highest percentage (20.9%), and states with lower Human Development Index (HDI) exhibited lower mortality rates. Females predominated with 61.3%, and there was a prevalence of deaths in older age groups (62.8% for ages 70 to 79 and 80 years or older). Individuals of mixed race and white ethnicity accounted for 86.23% of the deaths, and married and widowed marital statuses also showed the highest values (61.27%). The analyzed data contribute to healthcare intervention, as access to information determines disease patterns in society, enabling the development of targeted and effective public policies.